Multiplanar reformation computed tomography for carpal malalignment. (December 2019) - Schormans, Philip M. J.; Schots, Judith P. M.; Weijers, René E.; Loeffen, Daan V.; Poeze, Martijn; Hannemann, Pascal F. W.
Correct interpretation of scaphoid axial length and carpal malalignment is difficult owing to the complex geometry of the scaphoid. Traditional measurements, such as the scapholunate angle and radiolunate angle, have shown limited reproducibility. To improve the assessment of these measurements, we used multiplanar reformation computed tomography with added average intensity projection. Four measurements for scaphoid morphology and carpal alignment were independently measured by four observers on computed tomography scans of 39 consecutive patients who were treated conservatively for scaphoid fracture. Fleiss's kappa for categorical results showed substantial agreement for the measurements of the scapholunate and radiolunate angles. Intraclass correlation coefficients were significant for measurements of the axial length, scapholunate angle and radiolunate angle. Our results suggest that multiplanar reformation computed tomography with added average intensity projection is a reliable technique for assessment of scaphoid morphology and carpal alignment. Level of evidence : II